2014
DOI: 10.4141/cjas2013-139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing barley grain with graded levels of wheat bran on rumen fermentation, voluntary intake and nutrient digestion in beef cattle

Abstract: 2014. Effects of replacing barley grain with graded levels of wheat bran on rumen fermentation, voluntary intake and nutrient digestion in beef cattle. Can. J. Anim. Sci. 94: 129Á137. Abrasion-milled wheat bran (AMWB) is a relatively new by-product from wheat-based ethanol production. Few published studies are available on the nutritional value of this by-product feed for growing cattle. The objective of this trial was to evaluate the effects of replacing rolled barley with AMWB on apparent nutrient digestibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Therefore, the higher acetate concentration could be attributed to the high fiber content in the ML0 diet. The total VFA concentration did not differ among treatments, which might be the result of the same ratio of forage to concentrate of diets [44], or might be caused by the fact that the output of total VFA was equivalent to the amount of absorption in the rumen among treatments [45]. In the present research, the observed concentrations of propionate and the acetate to propionate ratio were not significantly different, probably because of the similar ruminal pH values caused by dietary-associated shifts [46].…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, the higher acetate concentration could be attributed to the high fiber content in the ML0 diet. The total VFA concentration did not differ among treatments, which might be the result of the same ratio of forage to concentrate of diets [44], or might be caused by the fact that the output of total VFA was equivalent to the amount of absorption in the rumen among treatments [45]. In the present research, the observed concentrations of propionate and the acetate to propionate ratio were not significantly different, probably because of the similar ruminal pH values caused by dietary-associated shifts [46].…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, increasing the ammonia level improves fibre digestion in the rumen. The total VFA concentrations were unaffected among the groups, which might be the result of the same ratio of forage to concentration of treatment diets 36 , or might be caused by the fact that the output of total VFA was equivalent to the amount of absorption in the rumen among all treatments 37 . In the present research, the observed concentrations of acetate and propionate, and the acetate to propionate ratio were not significantly different, probably because of the similar ruminal pH values caused by the dietary-associated shifts 38 .…”
Section: Discussionmentioning
confidence: 95%
“…Substrate composition affects the VFA concentration in the fermentation processes [36]. Consequently, the unaffected concentration of total VFA, acetate, and propionate, indicating that the fermentation pattern is similar, which could be explained by that all the substrate in the fermentation were wheat among different treatments.…”
Section: Discussionmentioning
confidence: 94%